A new species of Metallolophia Warren, 1895 (Lepidoptera: Geometridae: Geometrinae), and notes on M. opalina (Warren, 1893), from eastern Himalaya, India - Sondhi, Sanjay; Basu, Dipendra Nath; Sondhi, Yash; Kunte, Krushnamegh (Zootaxa, 2020)
A new species, Metallolophia taleensis, sp. nov., is described and illustrated from Tale Wildlife Sanctuary, Lower Subansiri District, Arunachal Pradesh, India, based on male specimens. A second species, Metallolophia opalina (Warren, 1893), is recorded from India after more than a century, extending its range eastwards into Arunachal Pradesh, India.